2022
DOI: 10.1177/26339137221083293
|View full text |Cite
|
Sign up to set email alerts
|

Collective intelligence as a public good

Abstract: We discuss measures of collective intelligence in evolved and designed self-organizing ensembles, defining collective intelligence in terms of the benefits to be gained through the exchange of information and other resources, as well as through coordination or cooperation, in the interests of a public good. These benefits can be numerous, from estimating a hard-to-observe cue to efficiently searching for resource. The measures should also account for costs to individuals, such as in attention or energy, and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 160 publications
2
14
0
Order By: Relevance
“…There may be additional incentives for exploration for novel solutions or ideas, for example, patents, social prestige, and other rewards associated with innovations [Giraldeau et al, 2017]. Our results also suggest that studies on collective behavior should consider the discrepancies between individual and collective goals, costs and benefits [Leonard and Levin, 2022]. Further, investigating how social learning and communication evolve in tandem with individual search strategies under different contexts can shed light on general aspects of collective behavior and sociality.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…There may be additional incentives for exploration for novel solutions or ideas, for example, patents, social prestige, and other rewards associated with innovations [Giraldeau et al, 2017]. Our results also suggest that studies on collective behavior should consider the discrepancies between individual and collective goals, costs and benefits [Leonard and Levin, 2022]. Further, investigating how social learning and communication evolve in tandem with individual search strategies under different contexts can shed light on general aspects of collective behavior and sociality.…”
Section: Discussionmentioning
confidence: 88%
“…The model also shows how strategies selected for foraging efficiency at the individual level may not always be beneficial for collective foraging. Instead, individual-level selection can lead to discrepancies between individual and collective search goals Leonard and Levin [2022] by favoring less-efficient exploitative strategies. We found that informed Lévy-like patterns such as those generated by ARS can restore and stabilize the balance between exploration and exploitation at both individual and group levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The private benefits allow the evolutionary emergence of forecasters, who then provide public benefits to all. Collective intelligence can be measured by the relative performance of individuals and groups (Leonard and Levin, 2022). The environmental stability and increased average payoffs that forecasting types often provide can therefore be seen as a form of collective intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…Large portions of the collective decision-making literature in swarm robotics are focused on discrete problems, such as the popular collective perception benchmark scenario [4]. Here we focus on a continuous consensus achievement problem [7], [8] in the form of a decentralized estimation scenario [9]. In our previous work we studied the effect of diverse information on the accuracy of collective estimation, which forms the exploration-exploitation tradeoff [1].…”
Section: Introductionmentioning
confidence: 99%